2022
DOI: 10.3389/fpls.2022.923880
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting microorganisms as biocontrol agents of plant diseases: Mechanisms, challenges and future perspectives

Abstract: Plant diseases and pests are risk factors that threaten global food security. Excessive chemical pesticide applications are commonly used to reduce the effects of plant diseases caused by bacterial and fungal pathogens. A major concern, as we strive toward more sustainable agriculture, is to increase crop yields for the increasing population. Microbial biological control agents (MBCAs) have proved their efficacy to be a green strategy to manage plant diseases, stimulate plant growth and performance, and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 219 publications
0
42
0
1
Order By: Relevance
“…However, there are still some gaps in the knowledge of bacteria-fungus interactions that can better direct their dual action in the field and that do not harm other endemic beneficial organisms. Other precautions that must be taken before releasing a biofungicide were recently proposed by other authors [ 22 ]. Finally, the search and characterisation of new species of PGPB and their anti- Botrytis compounds will continue to be a resource that should be explored with greater effort to have better and more sustainable agricultural practices for the sake of our planet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still some gaps in the knowledge of bacteria-fungus interactions that can better direct their dual action in the field and that do not harm other endemic beneficial organisms. Other precautions that must be taken before releasing a biofungicide were recently proposed by other authors [ 22 ]. Finally, the search and characterisation of new species of PGPB and their anti- Botrytis compounds will continue to be a resource that should be explored with greater effort to have better and more sustainable agricultural practices for the sake of our planet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternatives have been sought to eliminate or reduce the use of synthetic chemicals to control B. cinerea , including the use of microbial agents such as Trichoderma harzianum [ 17 ], T. viride , T. virens [ 18 ], Ulocladium spp. [ 19 ], Clonostachys rosea [ 20 ], Gliocladium catenulatum , Saccharomyces cerevisiae , Wickerhamomyces anomalus , Metschnikowia pulcherrima , and Aureobasidium pullulans [ 21 , 22 ], as well as diverse plant growth-promoting bacterial species (PGPB) [ 11 , 23 , 24 , 25 , 26 , 27 ]. This last group of beneficial bacteria, in addition to stimulating plant growth directly, can also antagonise fungal pathogens, such as B. cinerea, through various mechanisms [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms employed by plant-beneficial microorganisms to promote growth are involved in various ways. Specifically, they benefit plants directly by phytohormone production and modulation such as indole-3-acetic acid (IAA) and gibberellin (GA) [ 19 ], enhancement of nutrient acquisition including iron, phosphorus, and nitrogen elements, and production of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase [ 20 , 21 ]. It was reported that endosymbiont Piriformospora indica could promote tomato growth by elevating putrescine, IAA, and GA levels [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For several years, a great deal of money and manpower is invested to protect the crop plants from fungal pathogens for ensuring good quantitative and qualitative yield, but still, it remains as a burning problem. The potential issues as toxicity, environmental pollution and side effects on human health hinder the applicability of chemical agents for fighting the phytopathogens (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Commercialization of biological control agents for plant diseases is following a slow pace mainly due to their variable performances under different environmental conditions in the field, their host specificity and low efficacy to manage the disease (5) . The performance of a biocontrol agent depends on the survival rate in the soil, its compatibility with the crop plant, interaction with other soil microbial species and the environmental factors (1) . These limitations can be overcome if we can identify the biologically active compound from the antagonistic organism and extract it in the pure form.…”
Section: Introductionmentioning
confidence: 99%